The Healing Ministry as a Catalyst of the Growth of Christ Apostolic Church in Southwestern Nigeria, 1943-2000 (2014)
Divine Healing, which is healing without orthodox medicine, has over the years played a dominant role in the growth of Christ Apostolic Church (CAC) in Southwestern Nigeria. Despite this role, previous studies have focused on its theological significance and changing trends, with little emphasis on its impact on the growth of CAC Therefore, this study examined the healing ministry in CAC Southwestern Nigeria (1943-2000), with a view to assessing its large contributions to the numerical growth of the church in the areas of membership, size of ordained ministers and church branches. The study was premised on Kohlberg’s theory of growth and development. In-depth interviews were conducted with purposively selected 20 ministers, 20 evangelists, 30 faith-home workers, 20 church medical doctors, 30 male and 30 female members in selected healing centres of the church in Lagos, Ibadan, Ikeji-Arakeji, Efon-Alaaye, Ede and Akure, where CAC thrived. Also, 534 copies of a questionnaire were administered to purposively selected 349 members and 185 ministers in the centres. Church records at the General Headquarters in Ibadan were consulted. Data were subjected to historical analysis and percentage scores. Ignorance causing a lingering epidemic between 1925 and 1943 facilitated membership growth in CAC. Records from the church’s headquarters indicated that between 1943 and 1962, membership grew from 62,103 to 82,755 in Lagos, Ijebu-ode and Ibadan centres, due to healing testimonies traced to the survival of the epidemics. Church records, complemented by 58.0% of interview responses, indicated that between 1943 and 1959, over 50.0% of converts to CAC in the Ekiti and Ondo axis were attracted by healing. About 63.8% of the questionnaire respondents agreed that the membership size of 297,482 between 1963 and 1983 was connected to five dead people raised in Ijesaland. Despite this success, the death of 33 persons, compounded by government’s denial of death certificates to their families between 1959 and 1996 caused downward patronage for the CAC healing ministry. However, in 1983, the renewed emphasis on efficacy of water sourced from Ariran Brook at Ikeji-Arakeji which accounted for the healing of 40 persons between 1990 and 1992; the lift of embargo on orthodox medicine by the church authority in 1997; and improved services in the faith-homes, culminated in the membership swell of 500,000 in the year 2000. Increased healing campaigns and establishment of three seminaries in Ede, Lagos and Ile-Ife, facilitated ministerial growth between 1943 and 1962, raising the number of ministers from 24 to 40. Between 1963 and 1982, more healing manifestations increased the number to 402, and their impactful zeal for healing brought the number to 2,504 in year 2000. Church records at the headquarters indicated that healing practices progressively led to branch expansion: 76 (1943), 497 (1962), 1,602 (1982), and 4,682 (2000). The healing ministry in Christ Apostolic has largely contributed to the growth of Christ Apostolic Church in Southwestern Nigeria between 1943 and 2000. Thus, the healing ministry proved to be an indispensible instrument for membership drive, ministerial formation and church growth